Predicting Survival of Small Intestine Neuroendocrine Tumors: Experience From a Major Referral Center. Issue 4 (April 2019) - Kelly, Susheian; Aalberg, Jeffrey; Agathis, Alexandra; Phillips, Katherine; Haile, Sara; Haines, Kenneth; Kang Kim, Michelle; Divino, Celia M.
Abstract : Objective: Neuroendocrine tumors (NETs) comprise 41.8% of small intestine malignancies. The NET nomogram is a 15-item prognostic tool that includes relevant factors for guiding management decisions. This is the first external validation of this tool among American patients at a tertiary treatment center. Methods: Patients who underwent surgical intervention from 2005 to 2017 were screened by retrospective chart review. Nomogram scores were calculated following the methods outlined by Modlin et al ( Neuroendocrinology . 2010;92:143–157). Validation assessed the association between nomogram scores and survival using Wilcoxon test and Cox regression. Results: Among the 121 patients selected, the NET nomogram significantly predicted survival as a continuous variable ( P < 0.01) and when dichotomized using 83 points to distinguish low-risk versus high-risk groups ( P < 0.01). However, the nomogram was not universally applicable as even at our specialty center, variables such as chromogranin A and urinary 5-hydroxyindoleacetic acid are not routinely collected, whereas others, like tumor grade, do not reflect the most recently updated classifications. Conclusion: The NET nomogram accurately identified patients at low and high risk of death. However, revision to update prognosticators could improve its usefulness for predicting survival of small intestine NETs.